George P. Welsh papers - Welsh, George P., -1860.
Official journals, manuscript manual on sailing and astronomy (circa 1771), and printed material. Journals kept by Welsh on his midshipman cruises on the U.S.F. Brandywine, Mediterranean Squadron (1841-1842); U.S.S. Independence, Home Squadron (1843); U.S.S. Levant, Pacific Squadron (1843-1845); and U.S.S. Plymouth, East India Squadron (1848-1851). Journal kept on the U.S.S. Levant includes maps and sketches (profile), and the U.S.S. Plymouth journal includes extensive commentary on the negotiations and visits of U.S. special agent Joseph Balestier in Cochin China, Thailand, Subi Island, and Borneo.
Naval officer.
Forms part of: Naval Historical Foundation collection.
Keywords: Brandywine (Frigate); Independence (Ship : 1814-1913); United States. -- Navy. -- East India Squadron; United States. -- Navy. -- Mediterranean Squadron; United States. -- Navy. -- Pacific Squadron; Astronomy; Sailing; Borneo -- Foreign relations -- United States; Vietnam, Southern -- Foreign relations -- United States; Indonesia -- Foreign relations -- United States; Thailand -- Foreign relations -- United States; United States -- Foreign relations -- Borneo; United States -- Foreign relations -- Vietnam, Southern; United States -- Foreign relations -- Indonesia; United States -- Foreign relations -- Thailand; United States -- Foreign relations -- Vietnam; Vietnam -- Foreign relations -- United States; Balestier, Joseph; Levant (Ship); Plymouth (Ship); United States. -- Navy. -- Home Squadron; Naval officers